Exploring the Effects of Cyclosporin A to Isocyclosporin A Rearrangement on Ion Mobility Separation - Mácha, Hynek; Zápal, Jakub; Kuzma, Marek; Luptáková, Dominika; Lemr, Karel; Havlíček, Vladimír (Analytical chemistry, 2024)
Cyclosporin A (CycA) is a peptide secondary metabolite derived from fungi that plays a crucial role in transplantation surgery. Cyclic traveling wave ion mobility mass spectrometry (IM-MS) revealed an N → O peptidyl shift in singly protonated CycA to isocyclosporin A (isoA), whereas no such isomerization was observed for doubly protonated and sodiated molecules. CycA and isoA were able to be separated by considering doubly protonated precursors using a specific ion fragment. In parallel, sodium ion stabilization facilitated the simultaneous separation and quantitation of singly charged cyclosporin isomers with the limit of detection and coefficient of determination of 1.3% and 0.9908 for CycA in isoA and 1.0% and 0.9830 for isoA in CycA, respectively. Finally, 1H-13C gHSQC NMR experiments permitted parallel recording of up to 11 cyclosporin conformers. The ratios were determined by integrating the volume of cross-peaks of the upfield resonating hydrogen in the diastereotopic methylene group of sarcosine-3.
Keywords: cyklosporiny; Peptides; Cyclosporine; cyklosporin; isomerie; Isomerism; ionty; Ions; Cyclosporins; peptidy